Ressonàncies musicals en l'obra de Fontanella. - PUJOL I COLL, JOSEP (Scripta, 2018)
Referring to the Francesc Fontanella's poetry, the article first notes the presence of the composer Joan Cererols as a poet in Catalan at his Vexamen, a fact that has gone unnoticed in musicological circles. Then it links the poetry of Fontanella with musical genres, especially with the villancicos. Finally, it retrieves some melodies that, as contrafacta, fit with his lyrics to sing them.